FRI0161 PHARMACOKINETICS AND SAFETY OF A SINGLE ORAL DOSE OF PEFICITINIB (ASP015K) IN SUBJECTS WITH NORMAL AND IMPAIRED HEPATIC FUNCTION. (June 2019) - Miyatake, Daisuke; Shibata, Tomohisa; Toyoshima, Junko; Kaneko, Yuichiro; Oda, Kazuo; Nishimura, Tetsuya; Katashima, Masataka; Sakaki, Masashi; Inoue, Kazuaki; Ito, Takayoshi; Uchida, Naoki; Furihata, Kenichi; et al.
Abstract : Background: Peficitinib (ASP015K), a novel oral Janus kinase inhibitor, demonstrated efficacy as once-daily therapy for moderate–severe rheumatoid arthritis in a phase 2b study (NCT01649999 ) 1 and 2 phase 3 studies (NCT02308163 2 ; NCT02305849 ). 3 Mean urinary excretion of peficitinib accounted for 9–15% of the oral dose. 4 It produces 3 conjugated metabolites (H1, H2, H4), which show very weak in-vitro pharmacological action. Objectives: To assess pharmacokinetics (PK) and safety of a single oral dose of peficitinib 150 mg in subjects with normal and impaired hepatic function. Methods: This phase 1, open-label, single-dose, parallel-group study was conducted at six centres in Japan. Eligible subjects were aged 20–75 years, with body mass index ≥17.0–<30.0 kg/m 2 . Hepatic impairment was defined at screening using Child-Pugh classification: Class A, mild (5–6 points); Class B, moderate (7–9 points). Subjects with severe hepatic impairment (Child-Pugh classification Class C, 10–15 points) were excluded. Subjects received a single oral dose of peficitinib 150 mg under fasting conditions, based on daily dose in the 2 phase 3 studies. Blood samples for plasma PK analysis of peficitinib and its metabolites were collected before and up to 72 h post dose. Safety was assessed throughout the study. Results: 24 subjects were enrolled (70.8% male): 16 with impaired and 8 with normal hepatic function (Table 1 ); all received study medication according to protocol. The peficitinib concentration-time profiles from dosing to 72 h (Fig. 1 ), extrapolated to infinity (AUCinf ), and maximum concentration (Cmax ) were similar in subjects with normal and mildly impaired hepatic function; however, AUCinf and Cmax were increased in subjects with moderate hepatic impairment (Table 2 ). There was a trend of greater exposure to H1, H2 and H4 metabolites in subjects with mild or moderate hepatic impairment, except for H2 in moderate hepatic impairment, although geometric mean ratios versus subjects with normal function were variable (Table 2 ). One subject in each group experienced a total of 5 TEAEs (Table 3 ), all of which were considered drug-related except back pain. No serious TEAEs, deaths or clinically significant mean changes from baseline in clinical laboratory parameters were reported during the study. Conclusion: Peficitinib exposure in subjects with mild hepatic impairment was similar to that in subjects with normal hepatic function; subjects with moderate hepatic impairment had greater exposure. A single dose of peficitinib was well tolerated. References: [1] Takeuchi T, et al. Ann Rheum Dis 2016; 75: 1057–64; 2. Tanaka Y, et al. ACR/ARHP Annual Meeting 2018: Abstract 887; 3. Takeuchi T, et al. ACR/ARHP Annual Meeting 2018: Abstract 888; 4. Cao YJ, et al. Clin Pharmacol Drug Dev 2016;5:435–49 Acknowledgement: This study was sponsored by Astellas Pharma, Inc. Medical writing support was provided by Iona Easthope of Cello Health MedErgy and funded by Astellas Pharma, Inc. Disclosure of Interests: Daisuke Miyatake Employee of: Astellas Pharma, Inc., Tomohisa Shibata Employee of: Astellas Pharma, Inc., Junko Toyoshima Employee of: Astellas Pharma, Inc., Yuichiro Kaneko Employee of: Astellas Pharma, Inc., Kazuo Oda Employee of: Astellas Pharma, Inc., Tetsuya Nishimura Employee of: Astellas Pharma, Inc., Masataka Katashima Employee of: Astellas Pharma, Inc., Masashi Sakaki Grant/research support from: Astellas Pharma, Inc., Kazuaki Inoue Grant/research support from: Astellas Pharma, Inc., Takayoshi Ito Grant/research support from: Astellas Pharma, Inc., Naoki Uchida Grant/research support from: Astellas Pharma, Inc., Kenichi Furihata Grant/research support from: Astellas Pharma, Inc., Akinori Urae Grant/research support from: Astellas Pharma, Inc.